Pengembangan Media Pembelajaran Genially Menggunakan Model Problem Based Learning pada Pembelajaran Pendidikan Pancasila di Kelas V UPTD SDN 013829 Ledong Timur - Nurhasanah, Siti; Reinita, Reinita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research and development aims to determine the validity, practicality, and effectiveness of Genially interactive learning media based on the Problem Based Learning (PBL) model in the Pancasila Education learning in grade V of UPTD SDN 013829 Ledong Timur. This research is a type of development research (Research and Development) that adapts the ADDIE model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research are 23 fifth-grade students. The data collection techniques used were interviews, questionnaires, and tests, while the data analysis techniques employed qualitative and quantitative approaches. The research results show that the interactive learning media based on Genially with the PBL model received a validity score of 91.11% from material experts, language experts, and media experts, which falls into the 'very valid' category. The practicality assessment results from teachers were 94% and from students were 95.90%, both of which are categorized as 'very practical'. The effectiveness test results indicate a learning completeness percentage of 75%, which is classified as high. Thus, the Genially interactive learning media based on Problem Based Learning is declared valid, practical, and effective and is able to improve the learning outcomes of students in the subject of Pancasila Education.